Altered Fc galactosylation in IgG4 is a potential serum marker for chronic lung disease. Issue 3 (31st July 2018) - Heyder, Tina; Wiklundh, Emil; Eklund, Anders; James, Anna; Dahlén, Sven-Erik; Grunewald, Johan; Zubarev, Roman A.; Lundström, Susanna L.
Characterising chronic lung diseases is challenging. New, less invasive diagnostics are needed to decipher disease pathologies and subphenotypes. Fc galactosylation is known to affect IgG function, and is altered in autoimmune disorders and under other pathological conditions. We tested how well Fc glycans in IgG from bronchoalveolar lavage fluid (BALF) and serum correlated, and if the Fc glycan profile could reveal pulmonary inflammation. A shotgun proteomics approach was used to profile Fc glycans in serum and BALF of controls (n=12) and sarcoidosis phenotypes (Löfgren's syndrome (LS), n=11; and non-LS, n=12). Results were further validated in severe asthma (SA) (n=20) and published rheumatoid arthritis (RA) patient data (n=13) including clinical information. Intra-individually, Fc-galactosylation status of IgG1 (R 2 =0.87) and IgG4 (R 2 =0.95) correlated well between matrixes. Following GlycoAge-index correction, the ratio between agalactosylated and digalactosylated Fc glycans of IgG4 could distinguish sarcoidosis and SA from healthy and RA subjects with a mean±se area under the curve (AUC) of 78±6%. The AUC increased to 83±6% using the more chronic lung disease types (non-LS and SA) and most strikingly, to 87±6% for the SA subgroup. The results indicate that the Fc galactosylation status of IgG4 is a potential blood test marker for chronic lung inflammation. IgG4 Fc galactosylation correlates between serum and BALF (R 2 =0.95) and is a potential blood marker for chronic lung inflammation http://ow.ly/XaNd30k35wg